Impact of Maltreatment: Psychosocial Experience of Parentless School Going Adolescents - Hariharathamotharan Suppiah; Dilrukshi Abyesinghe; S. Jeevasuthan (Asian Social Work Journal, 2019)
The present study examines the impact of maltreatment among the Parentless School Going Adolescents (PSGAs) and their psychosocial experiences in Northern Provence in Sri Lanka. Prevalence of PSGAs’ exposure to maltreatment can be understood considering the size of PSGAs exposed and their experiences, how exposure impacts PSGAs psychosocial development, factors that increase risk or provide protection against the negative effects of exposure, and the types of interventions that can be implemented to mitigate harmful effects. Participants (PSGAs) were recruited from two districts; namely Kilinochchi and Mullaithivu. Participants with recent experiences and had psychosocial distress were examined. 30 cases [Female=18 (60%), Male=12 (40%)] and [Mean Age=14.7, SD=1.9], were recruited using purposive sampling techniques. An exploratory approach was adopted and semi-structured interview was conducted as the present study aims to have an in- depth understanding on various elements of maltreatment experiences. The questions were mostly open-ended and were intended to be used as a guide to explore or capture as much as possible the PSGAs’ thoughts and feelings about his/her experiences. Content analysis was used to identify common themes related to the objective. Twenty two cases (73.3%) were subject to maltreatment by care takers and their family members. The three most frequent types of relationships to the PSGAs were grandparents (9 cases), uncle (6 cases), and aunty (2 cases). Others included cousin (3), and brother-in-law (2). Maltreated by other people occurred in 21 cases (70 %). This included neighbor (7 cases), total stranger (4), friend’s parents (4), friend (2), teacher (2), priest (1) and servant (1). Many PSGAs faced with multiple maltreatment. Maltreatment occurs on the background of caretaker’s dysfunction and sociocultural factors. The findings underscore the need of providing support for caretakers so they can provide better care of PSGAs. Psychosocial intervention should be individualized to meet the needs of each PSGA. Further research is needed to clarify the issues of risk and protective factors in the post-war context in Northern Provence.